2020
DOI: 10.1371/journal.pone.0243276
|View full text |Cite
|
Sign up to set email alerts
|

Acute leucocyte, muscle damage, and stress marker responses to high-intensity functional training

Abstract: Background High-intensity functional training (HIFT) has become more popular, and the number of practitioners has increased; however, it remains unclear whether perturbations in the immune parameters occur, even after one single bout. Our aim was to examine acute leucocyte, muscle damage, and stress marker responses following a single ‘Cindy’ workout session, and compare the results between novice and experienced participants. Material and methods Twenty-three HIFT practitioners (age 31.0 ± 1.0 years) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…The main findings partially confirm the initial hypothesis, revealing 1) significant increases in blood lactate post-exercise; 2) an increase of CK concentration 24 h postexercise, returning to baseline levels 48 h post-exercise; 3) a significant change in the participants' perceived recovery status PRS for upper and lower limbs 24 h post-exercise when compared to baseline, with PRS values for the lower and upper limbs showing different rates of recovery at 24-and 48-h post exercise (with the lower limbs' PRS recovering slower than the PRS for the upper limbs). The findings corroborate previous studies that demonstrate the significant physiological, biochemical, and neuromuscular changes following a CrossFit ® session (Mate-Munoz et al, 2017;Gomes et al, 2020;Martinez-Gomez et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The main findings partially confirm the initial hypothesis, revealing 1) significant increases in blood lactate post-exercise; 2) an increase of CK concentration 24 h postexercise, returning to baseline levels 48 h post-exercise; 3) a significant change in the participants' perceived recovery status PRS for upper and lower limbs 24 h post-exercise when compared to baseline, with PRS values for the lower and upper limbs showing different rates of recovery at 24-and 48-h post exercise (with the lower limbs' PRS recovering slower than the PRS for the upper limbs). The findings corroborate previous studies that demonstrate the significant physiological, biochemical, and neuromuscular changes following a CrossFit ® session (Mate-Munoz et al, 2017;Gomes et al, 2020;Martinez-Gomez et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…EIMD affects all individuals depending upon the type, intensity, and duration of the exercise they undertake and training status of the individual [9,10]. Resistance training [11], high-intensity interval training [12], trail running [13,14], and downhill running [15] contribute to EIMD, leading to ultrastructural muscular disruption and an increase in inflammatory cytokine levels. Swelling of the affected limb, decreased range of motion (ROM), and impaired muscle force-producing capacity which can result from EIMD are undesirable [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The creatine kinase post-24 h after training was approximately 673 and 864 U/L for workouts 1 and 2, respectively. Gomes et al [ 30 ] also evaluated creatine kinase concentrations following a single workout (‘Cindy’—as many rounds as possible of 5 pull-ups, 10 push-ups, and 15 air squats in 20-min), and showed that creatine kinase concentrations increased post exercise (174.9 to 226.7 U/L) and remained elevated post-24 h (~ 270 U/L). The increase in the concentration occurred even though no external load was utilized, highlighting that the overall intensity of the session might be the key factor for creatine kinase changes.…”
Section: Discussionmentioning
confidence: 99%